A study to intensify local pepper consumption, with specific reference to pepper marketing boards' customers / Hugh Paul Samat - Samat, Hugh Paul (2003)
Pepper is rightly crowned the “King of Spice” for no other spice does so much for so many different foods from all over the world. This pungent, distinctive spice is often used three times in the same dish before the food is eaten: first as an ingredient in the preparation; then to correct or improve the overall seasoning during cooking; and finally at the dinner table if the dinner prefers more seasoning. Whatever the featured flavors of a recipe may be, there is a good chance that pepper will be present, complementing or contrasting them. And for quality, Sarawak pepper is the choice, be it black or white, whole or ground, fresh or pickled. It is known that Malaysia is one of the worlds' pepper producers for its quality pepper. However the local consumption of pepper among us is still low compare to other countries. A developed country like US, Germany, which is not a pepper producer countries has earn a title of highest pepper consumption per capita. Solution or campaign to increase the domestic consumption has been a popular topic among PMBs managers. The question on how to increase peoples consumption particularly focusing on 3 groups; industrial, institution and household, of course this people play a major role to help to boost up our fresh quality pepper consumption among Malaysian